Prevalence and risk factors associated with resistance-associated mutations to etravirine in a cohort of perinatally HIV-infected children (2013)
Etravirine is a second-generation non-nucleoside reverse transcriptase inhibitor (NNRTI) with reduced cross-resistance to first-generation NNRTIs. Because many perinatally HIV-infected patients have been treated with first-generation NNRTIs, they may have acquired resistance-associated mutations to etravirine (RAMe). We determined for the interval 1998–2009 the prevalence and factors associated with the presence of RAMe. Twenty-three of 66 (34.8%) children had RAMe; the most common were 181C (19.6%), 190A (7.5%), 98G (6%), 106I (4.5%), 179D (4.5%), 100I (3%), 181I (1.5%), 138A (1.5%) and 179T (1.5%). Eleven children with RAMe (17%) had a mutation score between 2.5 and 3.5 and 1 (1.5%) a score ≥4, indicating an intermediate and reduced response to etravirine. For each 1% increase in CD4% there is a 7% decrease in the odds of RAMe (OR 0.93; 95% CI 0.88–0.97; P < 0.01). History of nevirapine use (OR 8.95; 95% CI 2.31–34.73; P < 0.01) and Hispanic ethnicity (OR 4.76; 95% CI 1.03–21.87; P = 0.04) are significantly associated with risk of RAMe. RAMe are present and common among antiretroviral-experienced perinatally HIV-infected children without previous exposure to etravirine. This could limit the efficacy of etravirine-based regimens. In addition, our results underscore the importance of taking previous history of nevirapine into account for combined antiretroviral therapy regimens that contain etravirine.